The Precursor of the International Geophysical Year. The Norwegian-British-Swedish Antarctic Expedition - Domaas, Christel Misund (Lars Müller Publishers, 2021)
Book available at https://www.lars-mueller-publishers.com/antarctic-resolution . On the 11th of February 1950, the Maudheim wintering base was established on the Quar Ice Shelf at 71°02.6' S 10°55.5' W in Queen Maud Land, the territory claimed by Norway in 1939. This base would serve as the home of the Norwegian-British-Swedish Antarctic expedition. The idea of a Norwegian-British-Swedish expedition was conceived during the Second World War by the Swedish geographer Hans Wilhelmsson Ahlmann (1889–1974) to research global melting and glacial retreat in the southern hemisphere and to seek the causes and effects of the klimatförbettring – the “climate improvement” – he had registered in the northern hemisphere. The possible global effects and his belief in a Scandinavian obligation to participate in the quest for knowledge led him to focus on international cooperation to realise his plans. Ahlmann sought to continue the Swedish polar tradition and planned the expedition as a continuation of Otto Nordenskjöld’s prior expedition to Graham Land. He expected to attract British collaboration, leveraging on the fact that the country was in territorial dispute with Argentina and Chile in this region. The Royal Geographical Society accepted his offer of collaboration in September 1945.